An integrated fast-slow plant and nematode economics spectrum predicts soil organic carbon dynamics during natural restoration - Zhang, Chongzhe (The New phytologist, 2024)
© 2024 The Author(s). New Phytologist © 2024 New Phytologist Foundation.